1996
DOI: 10.1111/j.1439-0418.1996.tb01622.x
|View full text |Cite
|
Sign up to set email alerts
|

On the parasitization of the ladybird Coccinella septempunctata L. (Col., Coccinellidae)

Abstract: The present study deals with entomoparasites of Coccinella septempunctata L. in cereals, mainly in winter wheat. Sections of monthly sampled adult ladybirds during one year in different habitates at Staaken (Berlin) gave two peaks of parasitization with Perilitus coccinellae (Schrank) (Hym., Braconidae): (1) 33% in March (hibernation site); and (2) 12.5% in June (winter wheat). Populations of the ladybird investigated during the seasons in 1993 and 1994 in winter wheat at three locations (Berlin‐Staaken, Flämi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The oviposition of unfertile eggs by the non-exposed females paired with exposed males was expected, since host castration was found to be induced by D. coccinellae [19] (though, according to Kadono-Okuda et al [32], in the early phase of development, the parasitoid larvae may have a stimulatory effect on the maturation of the host’s female gonads).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oviposition of unfertile eggs by the non-exposed females paired with exposed males was expected, since host castration was found to be induced by D. coccinellae [19] (though, according to Kadono-Okuda et al [32], in the early phase of development, the parasitoid larvae may have a stimulatory effect on the maturation of the host’s female gonads).…”
Section: Discussionmentioning
confidence: 99%
“…Oviposition has to be very rapid to overcome host mobility and defensive reactions and the rate of parasitism may fluctuate considerably, depending on location, season and host species [16]. As a consequence of the parasitoid larval activity, the host gonads and fat body undergo great damage [19]. The lady beetles may, however, survive and even retain their ability to mate and lay eggs after parasitoid egression [20,21], but they are considerably weakened and almost paralyzed with parasitoid cocoon between their legs.…”
Section: Introductionmentioning
confidence: 99%
“…This enables the emerging larva to spin a cocoon between the host's legs and consequently gain protection beneath the aposematically coloured and chemically defended host body (Dheilly et al 2015). The virus-induced paralysis is temporary and ladybirds can sometimes recover and even resume their reproductive activity (Triltsch 1996;Maure et al 2014). If the intensity of paralysis is weak and/or its duration short, the role of parasitoid bodyguard played by the ladybird may be incomplete.…”
Section: Homalotylus Spp (Hymenoptera: Encyrtidae)mentioning
confidence: 99%
“…Due to the relatively little damage, the ladybirds usually survive the emergence of the parasitoid larva , although they are considerably weakened and paralyzed. Most of them die within the next few days, but some may recover (Timberlake 1916, Bryden & Bishop 1945, Walker 1961, Anderson et al 1986, Triltsch 1996. Triltsch (1996) found that some laboratory parasitized C. septempunctata females not only survived parasitization but also started laying eggs about 12 days after the emergence of the parasitoid larva.…”
Section: Host P References and P Arasitization R Atesmentioning
confidence: 99%